Radiopharmaceuticals for imaging and endoradiotherapy of neurotensin receptor‐positive tumors. (5th January 2018) - Maschauer, Simone; Prante, Olaf
Abstract : The neurotensin receptors are overexpressed in various tumor types, especially in highly progressive pancreatic tumors. As this cancer has a poor 5‐year survival prognosis, there is an urgent need to improve early diagnosis and treatment strategies. This review article provides an overview of the latest developments in radiopharmaceuticals for neurotensin receptor‐positive tumors, including peptidic and non‐peptidic radiopharmaceuticals, not only for SPECT and PET but also for endoradiotherapy. Abstract : This review article provides an overview of the latest developments in radiopharmaceuticals for neurotensin receptor‐positive tumors, including peptidic and non‐peptidic radiopharmaceuticals, not only for SPECT and PET but also for endoradiotherapy.